Polyphenols in Athletes’ Performance - Maricela DRAGOMIR; Cezar Ionuț BICHESCU; Dimitrie STOICA; Maricica STOICA (ACROSS)
Polyphenols are composed of thousands of compounds characterized by hydroxy groups attached to aromatic rings, being classified into flavonoids, lignans, phenolic acids, and stilbenes. They are frequently associated with different sports disciplines owing to their capability to enhance the body’s antioxidant capacity, and their anti-inflammatory properties, which can reduce exercise-induced inflammation, helping athletes to recover more quickly between training sessions. This article examines the most common polyphenols and their role in augmenting the body’s antioxidant capacity, essential for athletes across various sports disciplines.